KAJIAN ‘URF TERHADAP ASPEK HUKUM ADAT TRADISI ANTAR PAKATAN DALAM PESTA PERNIKAHAN SUKU MELAYU SAMBAS DI DESA SEPADU - Syarif, Muhammad; Bakar, Abu; Widiyawati, Ari (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
This research aims to examine: 1) The practice of the Antar Pakatan tradition in the wedding ceremonies of the Sambas Malay community in Sepadu Village, and 2) the ‘urf-based legal analysis of the custom of Antar Pakatan in the wedding ceremonies of the Sambas Malay community in Sepadu Village.The study employs a qualitative research method with field research and a normative-empirical approach. The data sources consist of primary and secondary sources: 1) primary sources include religious leaders, community members who marry off their children using the tradition, and other involved parties; 2) secondary sources include books, journals, and articles related to the study. Data collection techniques used are observation, interviews, and documentation. Data analysis applies the Miles and Huberman technique, which involves data reduction, data presentation, and drawing conclusions. Based on the analysis conducted, the researcher concludes that: 1) The Antar Pakatan tradition requires invitees to a wedding to bring one live chicken or poultry and a sack of rice as gifts for the hosting family. Besides serving as gifts, Antar Pakatan also helps alleviate the financial burden of wedding expenses. 2) The Antar Pakatan tradition can be categorized as ‘urf since it fulfills the requirements for customs or traditions to be recognized as ‘urf.